Liquid biopsy for pediatric diffuse midline glioma: a review of circulating tumor DNA and cerebrospinal fluid tumor DNA - Azad, Tej D. (Neurosurg Focus, 2020)
Diffuse midline glioma (DMG) is a highly malignant childhood tumor with an exceedingly poor prognosis and limited treatment options. The majority of these tumors harbor somatic mutations in genes encoding histone variants. These recurrent mutations correlate with treatment response and are forming the basis for molecularly guided clinical trials. The ability to detect these mutations, either in circulating tumor DNA (ctDNA) or cerebrospinal fluid tumor DNA (CSF-tDNA), may enable noninvasive molecular profiling and earlier prediction of treatment response. Here, the authors review ctDNA and CSF-tDNA detection methods, detail recent studies that have explored detection of ctDNA and CSF-tDNA in patients with DMG, and discuss the implications of liquid biopsies for patients with DMG.